The architecture of modern anti-unionism in Canada: Class struggle and the erosion of workers' collective freedoms. (September 2019) - Smith, Charles; Stevens, Andrew
Over the past four decades, governments have backed away from the promotion of collective bargaining in Canada resulting in a tendency towards anti-unionism. Examining this new reality, this article investigates two interrelated trends in Canadian anti-unionism over the last two decades in an effort to conceptualize the role of the state in regulating labour relations. First, we investigate legislative attempts to undermine or eliminate the ability of workers to collectively bargain and strike. Second, the article unpacks the political economy of anti-unionism in the private sector by focusing on the role of lobby groups that have shaped labour legislation. These two interrelated threads allow us to expose the relationship between employers and governments, which has threatened the strength of organized labour in the private and public sector and shaped a uniquely Canadian anti-unionism. Finally, we conclude by examining both the strengths and limitations of the unique fight-back strategies used by the labour movement, which has sought to elevate aspects of Canadian labour law to be protected by the Charter of Rights and Freedoms. This, we argue, offers restrictive possibilities for advancing collective bargaining rights in the existing labour relations framework.